Contribution of Trichoderma asperellum Formula Based on Red Sticky Rice to The Vegetative Growth of Rice - Annisya Putri; Azwir Anhar; Linda Advinda; Filza Yulina Ade (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Rice (Oryza sativa L.) is a strategic food commodity in Indonesia, with demand continuing to rise in line with population growth. Efforts to increase rice production through intensification often rely on the use of inorganic fertilizers, which have a negative impact on soil fertility. One alternative to reduce this dependence is the use of microbial-based biofertilizers, such as Trichoderma asperellum, which plays a role in improving nutrient uptake and plant growth. However, the formulation of T. asperellum in conventional media such as PDA is still ineffective in the field due to its relatively high cost. This study was conducted to examine the contribution of a red glutinous rice-based T. asperellum formula with the addition of ecoenzyme to the vegetative growth of paddy rice (Oryza sativa L.). The study was designed using a completely randomized design (CRD) with six treatments of formula composition and NPK fertilizer and five replicates. The parameters observed included plant height and number of tillers at 3, 5, and 7 weeks after planting (WAP). The data were analyzed using ANOVA and Duncan's test at a 5% level. The results showed that the treatments had a significant effect on the vegetative growth of rice. Treatment P3 (60% formula + 40% NPK) produced the highest plant height (131.43 cm) at 7 weeks after planting, while treatment P2 (80% formula + 20% NPK) produced the highest number of tillers (60.33 tillers per clump) in the fifth week. These findings indicate a synergy between the biological activity of T. asperellum and NPK fertilizer, as well as the potential for reducing the use of inorganic fertilizers without decreasing the vegetative growth of rice.